Sex estimation from reconstructed scapula models using discriminant function analysis in the Malaysian population. Issue 2 (4th March 2021) - Omar, Normaliza; Mohd Ali, Siti Hanum; Shafie, Mohamed Swarhib; Nik Ismail, Nik Azuan; Hadi, Helmi; Ismail, Rosnah; Mohd Nor, Faridah
ABSTRACT: Scapulae have been widely studied for its potential in differentiating sex in skeletal remains, especially when traditionally used sexually dimorphic bones were not available. The present work aimed to investigate sexual dimorphism of scapulae, and to develop and validate the population-specific metric standards of the Malaysian population using three-dimensional (3D) computed tomographic (CT) scapula models. Each scapula was measured for five variables with a digital caliper and analysed for independent T-test and discriminant analysis, where a leave-one-out cross-validation was applied. Moreover, a set of different samples (hold-out sample) was used to validate the established discriminant functions (DF). Consequently, all measurements showed significant differences between males and females (p < 0.001) and morphological breadth was discovered as the most sexually dimorphic scapulae measurements. Six DFs with classification accuracy ranging from 84.4% to 93.1% were generated. From the functions, stepwise DF predicted the highest classification accuracy. Additionally, the stepwise DF exhibited 95% classification accuracy when tested on the hold-out sample compared to univariate DFs which showed 82.5–92.5% accuracy. In conclusion, the virtual 3D scapulae models were sexually dimorphic, and the discriminant functions were significant in identifying skeletonized remains using scapulae bone in the Malaysian population.